1990
DOI: 10.2307/3430972
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Bulk Infrared Modes of Crystalline and Amorphous Silica Particles: A Study of the Relation of Surface Structure to Cytotoxicity of Respirable Silica

Abstract: Surface IR (infrared) modes of crystalline and fumed (amorphous) silica particles, calcined at temperatures up to 1095°C, have been studied by Fourier transform infrared spectroscopy. The ability of these same particles to lyse cells has been measured by a hemolysis protocol. The untreated crystalline and amorphous materials differ by a factor of 40 in specific surface area, and the intensity per unit mass ofthe sharp surface silanol band near 3745 cm-' in the amorphous material is an order of magnitude larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
6
23
0
Order By: Relevance
“…The various crystalline silica polymorphs exhibit remarkable differences in their pathogenic potential related to differences in crystal structure (1,3,8,(19)(20)(21). Even specimens of the same silica polymorph, e.g., cristobalite dusts of different origin (22,23) (22,33). Correspondingly, the membranolysis potential decreases (33,34).…”
Section: Physicochemical Factors Influencing Surface Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The various crystalline silica polymorphs exhibit remarkable differences in their pathogenic potential related to differences in crystal structure (1,3,8,(19)(20)(21). Even specimens of the same silica polymorph, e.g., cristobalite dusts of different origin (22,23) (22,33). Correspondingly, the membranolysis potential decreases (33,34).…”
Section: Physicochemical Factors Influencing Surface Reactivitymentioning
confidence: 99%
“…Even specimens of the same silica polymorph, e.g., cristobalite dusts of different origin (22,23) (22,33). Correspondingly, the membranolysis potential decreases (33,34). The reversible adsorption of water, reported in Figure 1 for cristobalite heated at different temperatures, measures the extent of silanols patches, i.e., the extent of hydrophilic sites (18).…”
Section: Physicochemical Factors Influencing Surface Reactivitymentioning
confidence: 99%
“…Similarly, another critical analysis that considered all physicochemical characteristics like particle size, specific surface areas, experimental uncertainties 32) indicated a slight difference between the cytotoxicity of the three most common crystalline forms of silica (quartz, cristobalite and tridymite) when compared on the basis of equal number of particle number and surface area. The toxicity of crystalline silica can be markedly reduced by surface-modifications using a coating on the particle surface 7) .…”
Section: Methods To Characterize Silica Surfacesmentioning
confidence: 99%
“…We collected data with a VG HB5 field emission scanning transmission electron microscope (STEM), operated at 100 keV, with a probe size of 20 A. We conducted X-ray analysis using an energy dis-AM dCI am -, .. 9 & a M persive X-ray analyzer through the characteristic excitation of X-rays caused by energy losses from the inelastic collisions of electrons with atoms. Elements of atomic number 5 (boron) and greater can be detected by this approach.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in vitro studies of the membranolytic activity and cytotoxicity of mineral dust particles have shown no unique relationship with the bulk concentration of quartz in such dusts (3)(4)(5). On the other hand, many in vitro and in vivo studies of the effect on cytotoxicity of the surface characteristics of mineral particles have shown positive correlations with different related variables (6)(7)(8)(9). Also, Rehn et al (10) have shown that the presence of admixed minerals affects the rate of elimination of inhaled dusts from the lung.…”
mentioning
confidence: 99%